Strategic alliances in container liner shipping - Wiedmer, Robert; Panayides, Photis (My University, 2011)
The economic crisis in the years between 2008 and 2010 has demonstrated the necessity for substantial adjustments on behalf of container lines. Capacities were shifted quickly to emerging and less affected markets allowing a faster recovery of globally organized companies. This paper illustrates the dynamics in the container shipping market. Alongside the main characteristics of the Top 20 ocean shipping companies, liner services are described. These services are classified by geographic coverage and vessel deployment. In addition, this paper provides a better understanding of the collaboration among service providers. Starting from a general framework of co-operative liner services, in-depth analyses of the global alliances in liner shipping are obtained. These formations - Grand Alliance, New World Alliance and CKYH Alliance - are compared with alternative forms of collaboration in the liner shipping industry. The analysis of alliance announcements which are related to operational and strategic changes indicates that the "global alliances" cannot be regarded as closed corporate-like entities. In effect, service agreements are not only negotiated with the focal members of the specific alliance. Instead, every service is arranged individually and under specific conditions. By understanding the dynamics within alliances, we are able to develop an assessment relating to the stability of collaborations. Ultimately, these insights direct us to several paths for future research
Keywords: Liner shipping; Strategic alliance